A Morphological Analysis Of Derivational Affixes (Prefix) Un- And Dis- Used In An English-Indonesian Dictionary By John M. Echols And Hasan Shadily - Athoriah, Nurdiana; , Drs. Sigit Haryanto, M.Hum; , Siti Fatimah, S. Pd, M. Hum (2013)
This research aims at clarifuing the differences and similarities on the usage and the functions, also describing the characteristics between prefix un- and disi used iu an English-Indonesian dictionary by John M. Echols and Hasan Shadifu. The type of research is qualitative qualitative, The object of the study is affixes in prefix un- and dis- in an English-Indonesion dictionary. The data are words containing affixes found an English-Indonesian dictionary. The data collection method employed by rnriter is reading, selecting, collecting, and classiSing the affixes, especially prefix un- and dis- in an English-Indonesian dictionary by John M. Echols and Hasan Shadily. The results of this research are as follows: the imilarities the usage between prefix un- and dis- are (1) both ofprefixes un- and dis- can form noun, verb, and adjective, (2) they can be changed from noun iato verb category, (3) they are dervational affrxes. The diffiences the usage between prefix un- and dis are (l) prefix un- is often followed by adjective category, although prefix dis- is often followed by noun category, (2) prefix un- can be formed from noun into adective category and verb into noun, although prefix dis' can be formed from adjective into verb category, (3) prefix un- can change from adverb into adverb category. The similarity in aword used prefixes un- and dis-, although the difference is they have tlre differences meaning. The characteristics prefix un- is followed by the all of alphabet, except consonant [x]. Although prefix dis- is Prefix dis- can not be followed by consonant [d], [i], [k], [m], [n], [t], [v], [w], [xl, [yl, and [z]. The functions is form noun, verb, and adjective.